Socioeconomic position, referral and attendance to rehabilitation after a cancer diagnosis: A population-based study in Copenhagen, Denmark 2010–2015. (4th May 2019) - Oksbjerg Dalton, Susanne; Halgren Olsen, Maja; Moustsen, Ida Rask; Wedell Andersen, Carina; Vibe-Petersen, Jette; Johansen, Christoffer
Abstract: Background: Implementation of new cancer services may lead to socioeconomic differences in uptake and despite reports of more unmet needs among patients with low socioeconomic position studies have found that these patients receive less rehabilitation. We aimed to investigate associations between indicators for socioeconomic position and referral as well as attendance to rehabilitation for cancer. Methods: Through the Danish Cancer Registry, we identified all persons diagnosed with cancer in Copenhagen municipality 2010–2015 and obtained information on referral to and visits at the municipal rehabilitation center from municipal records. We linked the population with information on socioeconomic information and vital status through national registries. Associations were analyzed using multivariate Cox regression models. Results: Among 13, 059 persons diagnosed with cancer a total of 2523 were referred for rehabilitation within 2.5 years from diagnosis. Compared to persons with short education, men and women with long education and men with medium education had higher adjusted hazard ratios (HR) for being referred to rehabilitation (Long: HR-men, 1.30 (95% CI: 1.06–1.59) and HR-women, 1.33 (95% CI: 1.15–1.53; Medium: HR-men, 1.23 (95% CI: 1.02–1.49)). Both men and women with children living at home had higher HR of referral (HR-men, 1.23 (95% CI: 1.00–1.52) and HR-women, 1.28 (95% CI: 1.11–1.48)). Among patients referred to rehabilitation, 81% attended a visitation consultation. Long education was associated with attendance in both genders while in men, medium education and in women high income, respectively was associated with attendance. Conclusion: Clear socioeconomic differences in referral and attendance to rehabilitation services indicate that socioeconomic inequality exists in patients' transition from cancer treatment into post-treatment care. Systematic needs assessment and clarification of wish for rehabilitation should be a requisite for all cancer patients independent of their socioeconomic position.